2002
DOI: 10.1055/s-2002-23157
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep and Academic Performance

Abstract: Poor school performance by adolescent students has been attributed in part to insufficient sleep. It is recognized that a number of factors lead to diminished total sleep time and chief among these are early school start times and sleep phase delay in adolescence. Political initiatives are gaining momentum across the United States to require later school start times with the intent of increasing total sleep time and consequently improving school performance. Later school start times come with significant costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…TST did not correlate with self-reported grade point average, while earlier bed times and wake times did correlate with higher grades. The lack of correlation of TST with grades mirrors findings of a prior report using similar methods [15]. However, the published literature contains many studies that have demonstrated the importance of total sleep time for full enhancement of intellectual functioning as well as student safety behind the wheel [16].…”
Section: Discussionmentioning
confidence: 62%
“…TST did not correlate with self-reported grade point average, while earlier bed times and wake times did correlate with higher grades. The lack of correlation of TST with grades mirrors findings of a prior report using similar methods [15]. However, the published literature contains many studies that have demonstrated the importance of total sleep time for full enhancement of intellectual functioning as well as student safety behind the wheel [16].…”
Section: Discussionmentioning
confidence: 62%
“…This was further supported by the current finding that performance in both English and Mathematics were associated with the feeling of sleepiness on rising in the morning (p<0.05). Previous study by Eliasson et al [35] found no correlation between sleep duration and academic performance, and we suspected that may possibly be due to the fact that sleepiness was not studied. Further studies about the relationship between sleep duration and academic performance should also analyze the potential effect of daytime sleepiness.…”
Section: Discussionmentioning
confidence: 79%
“…While the association between EDS and snoring were well reported [35,28], no previous studies identified bruxism as a factor for EDS. The current study found that students with EDS were three times more likely to have bruxism.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, in one study involving 1000 high school students and 200 middle school students, there was no correlation between sleep time and academic performance measured by students' self-reported grade point average. This finding was consistent from 7th through 12th grades [11]. In light of these contradictory findings, which may mainly be due to differences in sample sizes, large adolescent cohorts are needed to examine if reports of sleep disturbances and short sleep duration are linked to academic success in school.…”
Section: Introductionmentioning
confidence: 71%
“…Another study demonstrated in children that experimental sleep restriction (i.e., 1 h less sleep each night over four consecutive nights) led to impaired math fluency and attentional deficits [5]. However, although fewer in number, there are also studies that did not find evidence for an association of insufficient sleep with academic performance [11,12]. For instance, in one study involving 1000 high school students and 200 middle school students, there was no correlation between sleep time and academic performance measured by students' self-reported grade point average.…”
Section: Introductionmentioning
confidence: 99%